A nanofiber membrane, and a method of making and using the same
Patent Information
- Application Number
- CN202311580611.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-24
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-24
AI Technical Summary
尽管它能够获高分离性能,但分离乳液体积少且很难从油/水乳液中回收高附加值的油类资源
[0020]1、本发明通过在亲水纳米纤维表面构筑超薄疏水层,即通过静电纺丝技术将含第一硅烷类单体负载在亲水基体外表面,进而通过第二硅烷类单体与亲水基体表面的第一硅烷类单体的硅烷基团的桥接作用,在本体亲水纳米纤维表面形成超薄疏水界面层,提升纳米纤维膜的抗污性能的同时实现油相的回收;
Smart Images

Figure CN117797650B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oil-water separation membrane preparation technology, and particularly relates to a nanofiber membrane, its preparation method and application. Background Technology
[0002] To rapidly clean contaminated water and obtain high-purity recovered oil, various methods have been developed, such as membrane separation, foam flotation, and selective adsorption. Among these, membrane filtration based on controllable surfaces with superwetting properties has become a promising solution due to its potential for highly selective separation of oil / water mixtures and large-scale recovery. Currently, efficient separation of oily wastewater mainly relies on physical retention mechanisms, which allow the continuous phase to pass through the membrane while the dispersed phase is retained. Although this method can achieve high separation performance, it results in small emulsion volumes and makes it difficult to recover high-value-added oil resources from oil / water emulsions. Furthermore, emulsified oil droplets exhibit high stability under the action of emulsifiers, making them difficult to effectively capture and demulsify on the membrane surface. Gradually enriched emulsified oil droplets further emulsify, increasing the viscosity of the emulsion and making separation more difficult. Designing high-performance separation membranes to simultaneously achieve water purification and oil collection during the separation of oil / water emulsions is of great significance. Summary of the Invention
[0003] The purpose of this invention is to provide a nanofiber membrane, its preparation method, and its application. This invention provides a nanofiber membrane constructed from Janus-like structured nanofibers and its preparation method. In the obtained heterogeneous wettable nanofibers, the hydrophobic layer can adsorb and diffuse demulsified oil droplets, freeing up membrane pore space, thereby ensuring a relatively stable flux of the continuous phase (water). More importantly, the shear force of the aqueous phase can directly act on the coalesced oil phase. At the same time, due to the directional transport effect, water can be transferred to the middle of the hydrophobic layer and the nanofiber substrate, which will further facilitate the release of oil from the membrane.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is: a method for preparing a nanofiber membrane, the preparation method specifically including the following steps:
[0005] S1. Weigh out the first silane monomer and the hydrophilic polymer and dissolve them in solvent A to obtain a mixed spinning solution;
[0006] S2. The mixed spinning solution obtained in step S1 is used to prepare a fiber membrane by electrospinning, phase inversion or melt spinning.
[0007] S3. Hydrolyze the fiber membrane obtained in step S2 to obtain a hydrolyzed fiber membrane;
[0008] S4. Weigh out the second silane monomer and the inorganic acid and dissolve them in solvent B to obtain a second silane monomer solution;
[0009] S5. Place the hydrolyzed fiber membrane obtained in step S3 into the second silane monomer solution obtained in step S4, then transfer it to a constant temperature and humidity chamber for reaction, and then take it out and air dry to obtain a nanofiber membrane.
[0010] Preferably, in step S1, the first silane monomer is selected from one or more of allyltriethoxysilane, (3-epoxypropoxypropyl)triethoxysilane, vinyltriethoxysilane, and allyloxytrimethylsilane; the hydrophilic polymer is selected from one or more of polyacrylonitrile, polyvinyl alcohol, polylactic acid, polyurethane, polymethyl methacrylate, polypropylene, and polyvinyl chloride; and the solvent A is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, toluene, acetone, n-hexane, and water.
[0011] Preferably, in step S1, the mass ratio of the first silane monomer, the hydrophilic polymer, and solvent A is (0.5-2):(4-30):(70-95).
[0012] Preferably, in step S3, the hydrolysis parameters are as follows: the hydrolysis temperature is 20-80℃, and the hydrolysis time is 20-120min.
[0013] Preferably, in step S4, the second silane monomer is selected from one or more of methyltrichlorosilane, dimethyldimethoxysilane, dimethyldichlorosilane, dodecylpentasiloxane, and diphenyldichlorosilane; the inorganic acid is selected from one or more of citric acid, glacial acetic acid, hydrochloric acid, sulfuric acid, and nitric acid; and the solvent B is selected from one or more of ethanol, isopropanol, methanol, n-hexane, toluene, dichloromethane, chloroform, and acetone.
[0014] Preferably, in step S4, the mass ratio of the second silane monomer, the inorganic acid and the solvent B is (1-30):(1-10):(60-98).
[0015] Preferably, the specific steps of step S5 are as follows: the nanofiber membrane after hydrolysis in step S3 is placed in the second silane monomer solution obtained in step S4 for 1-60 min, and then transferred to a constant temperature and humidity chamber with a temperature of 20-80℃ and a humidity of 10-90% for 10-180 min. After that, it is taken out and dried at 10-50℃ to obtain the nanofiber membrane.
[0016] The second objective of this invention is to provide a nanofiber membrane prepared by the above-described preparation method, wherein the nanofiber membrane has a heterogeneous wettability interface, the heterogeneous wettability interface comprising a hydrophilic nanofiber body and a hydrophobic layer wrapped around the surface of the hydrophilic nanofiber, the hydrophobic layer being a nanolayer with a thickness of less than 10 nm, and the diameter of the nanofibers in the nanofiber membrane being 20-1000 nm.
[0017] Preferably, the parameters of the nanofiber membrane are as follows: the water contact angle is 0°, the water droplet wetting time is less than 10s, and the underwater oil contact angle is greater than 120° and less than 150°.
[0018] A third objective of this invention is to provide an application of the aforementioned nanofiber membrane in the field of oil-water separation.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. This invention constructs an ultrathin hydrophobic layer on the surface of hydrophilic nanofibers, that is, by using electrospinning technology to load a first silane monomer onto the outer surface of a hydrophilic matrix, and then through the bridging effect of the second silane monomer and the silane group of the first silane monomer on the hydrophilic matrix surface, an ultrathin hydrophobic interface layer is formed on the surface of the bulk hydrophilic nanofibers, thereby improving the antifouling performance of the nanofiber membrane while realizing the recovery of the oil phase.
[0021] 2. This invention constructs an ultrathin hydrophobic layer on the outer surface of hydrophilic nanofibers, providing a destination for the aqueous and oil phases in an emulsion. The hydrophilic nanofibers ensure that the aqueous phase can wet the membrane substrate and allow the continuous aqueous phase to permeate through the membrane pores. The hydrophobic layer adsorbs and diffuses demulsified oil droplets along the nanofiber surface, freeing up membrane pore space and thus ensuring a relatively stable flux of the continuous phase (water). More importantly, the shear force of the aqueous phase can directly act on the aggregated oil phase. Simultaneously, due to the directional transport effect, water can transfer to the space between the hydrophobic layer and the nanofiber substrate, which further facilitates the release of oil from the membrane, ultimately achieving efficient demulsification, long-lasting anti-fouling oil-water separation, and simultaneous recovery of both oil and aqueous phases.
[0022] 3. Compared to existing oil-water separation membrane strategies, the Janus-like nanofiber membrane constructed by the present invention primarily relies on physical sieving for separation. In this process, the dispersed phase is typically excluded, while the continuous phase permeates through the membrane. The bottleneck of this technology is the unavoidable membrane fouling problem, requiring frequent membrane cleaning. Significant efforts have been made to address this issue, mainly based on the hydration layer effect. While this strategy can effectively separate oily wastewater, it struggles to achieve petroleum recovery. Consequently, the demulsified oil phase flows back to the feed liquid side, further increasing solution viscosity and exacerbating membrane fouling. The Janus-like nanofiber membrane constructed by the method described in this application exhibits heterogeneous wettability. Combined with the coalescence-demulsification separation mechanism, it can effectively demulsify emulsified oil droplets and allow them to permeate through the membrane along with the aqueous phase, resulting in a stratified oil and aqueous phase. Notably, the oil phase transfers from the membrane pores to the membrane substrate, further creating space for the aqueous phase to permeate. Ultimately, this achieves a stable and continuous permeate flux while simultaneously recovering both the aqueous and oil phases. The nanofiber membrane constructed from Janus-like nanofibers provided by the method of this invention exhibits a permeation flux of over 1200 L / m² for oil-in-water emulsions. -2 h -1 bar -1 With a separation rate of over 99.5%, a continuous operating time of over 10 hours, a processing capacity of oil-in-water emulsions, and an oil phase recovery rate of over 80%, it has broad application prospects in oil-water separation and the treatment of other industrial wastewater. Attached Figure Description
[0023] Figure 1 This is a scanning electron microscope (SEM) image of the polyacrylonitrile nanofiber membrane prepared in Comparative Example 1 of the present invention.
[0024] Figure 2 This is a scanning electron microscope (SEM) image of the vinyltriethoxysilane-doped polyacrylonitrile nanofiber membrane prepared in Comparative Example 2 of the present invention.
[0025] Figure 3 This is a scanning electron microscope (SEM) image of a polyacrylonitrile nanofiber membrane constructed from Janus-like nanofibers obtained in Example 1 of the present invention.
[0026] Figure 4 The thickness of the hydrophobic layer of the polyacrylonitrile nanofiber membrane constructed from the Janus-like structured nanofibers obtained in Example 1 of this invention.
[0027] Figure 5 The water contact angle (WCA) of the nanofiber membranes prepared in Comparative Examples 1, 2 and 1 of this invention varies with time.
[0028] Figure 6The underwater oil contact angle (UOCA) of the nanofiber membranes prepared in Comparative Examples 1, 2 and 1 of this invention is shown.
[0029] Figure 7 The long-term separation flux of the polyacrylonitrile nanofiber membranes constructed from the Janus-like structure nanofibers obtained in Comparative Examples 1, 2 and 1 of this invention is shown. Detailed Implementation
[0030] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0031] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0032] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This application specification and embodiments are merely exemplary.
[0033] The first objective of this invention is to provide a method for preparing nanofiber membranes, specifically including the following steps:
[0034] S1. Weigh out the first silane monomer and the hydrophilic polymer and dissolve them in solvent A to obtain a mixed spinning solution;
[0035] S2. The mixed spinning solution obtained in step S1 is used to prepare a fiber membrane by electrospinning, phase inversion or melt spinning.
[0036] S3. Hydrolyze the fiber membrane obtained in step S2 to obtain a hydrolyzed fiber membrane;
[0037] S4. Weigh out the second silane monomer and the inorganic acid and dissolve them in solvent B to obtain a second silane monomer solution;
[0038] S5. The hydrolyzed fiber membrane obtained after hydrolysis in step S3 is placed in the second silane monomer solution obtained in step S4, and then transferred to a constant temperature and humidity chamber for reaction. After reaction, it is taken out and dried to obtain a nanofiber membrane.
[0039] In a specific embodiment, in step S1, the first silane monomer is selected from one or more of allyltriethoxysilane, (3-epoxypropoxypropyl)triethoxysilane, vinyltriethoxysilane, and allyloxytrimethylsilane; the hydrophilic polymer is selected from one or more of polyacrylonitrile, polyvinyl alcohol, polylactic acid, polyurethane, polymethyl methacrylate, polypropylene, and polyvinyl chloride; and the solvent A is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, toluene, acetone, n-hexane, and water.
[0040] In a specific embodiment, in step S1, the mass ratio of the first silane monomer, the hydrophilic polymer, and solvent A is (0.5-2):(4-30):(70-95).
[0041] In a specific embodiment, the parameters for hydrolysis in step S3 are as follows: the hydrolysis temperature is 20-80℃, and the hydrolysis time is 20-120min.
[0042] In a specific embodiment, in step S4, the second silane monomer is selected from one or more of methyltrichlorosilane, dimethyldimethoxysilane, dimethyldichlorosilane, dodecylpentasiloxane, and diphenyldichlorosilane; the inorganic acid is selected from one or more of citric acid, glacial acetic acid, hydrochloric acid, sulfuric acid, and nitric acid; and the solvent B is selected from one or more of ethanol, isopropanol, methanol, n-hexane, toluene, dichloromethane, chloroform, and acetone.
[0043] In a specific embodiment, in step S4, the mass ratio of the second silane monomer, the inorganic acid, and the solvent B is (1-30):(1-10):(60-98).
[0044] In a specific embodiment, the specific steps of step S5 are as follows: the nanofiber membrane after hydrolysis in step S3 is placed in the second silane monomer solution obtained in step S4 for 1-60 min, and then transferred to a constant temperature and humidity chamber with a temperature of 20-80℃ and a humidity of 10-90% for 10-180 min. After that, it is taken out and dried at 10-50℃ to obtain the nanofiber membrane.
[0045] The second objective of this invention is to provide a nanofiber membrane prepared by the above-described method, wherein the nanofiber membrane has a heterogeneous wettability interface, the heterogeneous wettability interface comprising a hydrophilic nanofiber body and a hydrophobic layer wrapped around the surface of the hydrophilic nanofiber, the hydrophobic layer being a nanolayer with a thickness of less than 10 nm, and the diameter of the nanofibers in the nanofiber membrane being 20-1000 nm.
[0046] In a specific embodiment, the parameters of the nanofiber membrane are as follows: the water contact angle is 0°, the water droplet wetting time is less than 10s, and the underwater oil contact angle is greater than 120° and less than 150°.
[0047] The technical effects of the present invention will be described below with reference to specific embodiments.
[0048] Example 1
[0049] 1) Weigh a certain amount of vinyltriethoxysilane and polyacrylonitrile and dissolve them in N,N-dimethylacetamide to prepare a mixed spinning solution, wherein the mass ratio of vinyltriethoxysilane and polyacrylonitrile dissolved in N,N-dimethylacetamide is 1:4:95;
[0050] 2) Fiber membranes are prepared using electrospinning technology;
[0051] 3) The fiber membrane was placed in water at 80℃ for 20 minutes to hydrolyze and obtain a hydrolyzed fiber membrane;
[0052] 4) Weigh a certain amount of dimethyldimethoxysilane and sulfuric acid, and dissolve them in isopropanol to prepare a dimethyldimethoxysilane solution of a certain concentration, wherein the mass ratio of dimethyldimethoxysilane, sulfuric acid and isopropanol is 1:1:98.
[0053] 5) After placing the hydrolyzed fiber membrane obtained in step 3) in a dimethyldimethoxysilane solution for 1 min, it was transferred to a constant temperature and humidity chamber at 20℃ and 10% humidity for 3 h. After taking it out, it was dried at 10℃ to obtain the nanofiber membrane constructed from Janus-like nanofibers.
[0054] Example 2
[0055] 1) Weigh a certain amount of allyltriethoxysilane and polylactic acid and dissolve them in acetone to prepare a mixed spinning solution of a certain concentration, wherein the mass ratio of allyltriethoxysilane, polylactic acid and acetone is 0.5:4:94.5;
[0056] 2) Fiber membranes are prepared using electrospinning technology;
[0057] 3) Hydrolyze the fiber membrane in water at 60℃ for 1 hour;
[0058] 4) Weigh a certain amount of dodecylpentasiloxane and nitric acid, and dissolve them in methanol to prepare a dodecylpentasiloxane solution of a certain concentration, wherein the mass ratio of dodecylpentasiloxane, nitric acid and methanol is 10:5:85;
[0059] 5) After hydrolyzing the fiber membrane, place it in a dodecylpentasiloxane solution for 30 minutes, then transfer it to a constant temperature and humidity chamber at 80°C and 50% humidity for 10 minutes. Remove it and air dry it at 25°C to obtain the nanofiber membrane constructed from Janus-like nanofibers.
[0060] Example 3
[0061] 1) Weigh a certain amount of (3-epoxypropoxypropyl)triethoxysilane and polymethyl methacrylate and dissolve them in chloroform to prepare a mixed spinning solution, wherein the mass ratio of (3-epoxypropoxypropyl)triethoxysilane, polymethyl methacrylate and chloroform is 2:20:80.
[0062] 2) Fiber membranes are prepared using electrospinning technology;
[0063] 3) Place the fiber membrane in water at 30℃ for 30 minutes to hydrolyze;
[0064] 4) Weigh a certain amount of diphenyldichlorosilane and citric acid, and dissolve them in n-hexane to prepare a diphenyldichlorosilane solution of a certain concentration, wherein the mass ratio of diphenyldichlorosilane, citric acid and n-hexane is 30:10:60;
[0065] 5) After hydrolyzing the fiber membrane, place it in a diphenyl dichlorosilane solution for 30 min, then transfer it to a constant temperature and humidity chamber at 40℃ and 60% humidity for 35 min. Remove it and air dry it at 40℃ to obtain the nanofiber membrane constructed from Janus-like nanofibers.
[0066] Example 4
[0067] 1) Weigh a certain amount of allyloxytrimethylsilane and polyvinyl alcohol and dissolve them in a mixed solvent of water and toluene to prepare a mixed spinning solution, wherein the mass ratio of allyloxytrimethylsilane, polyvinyl alcohol and water and toluene is 0.5:15:84.5;
[0068] 2) Fiber membranes are prepared using electrospinning technology;
[0069] 3) Place the fiber membrane in water at 50℃ for 100 minutes to hydrolyze;
[0070] 4) Weigh a certain amount of methyltrichlorosilane and glacial acetic acid, and dissolve them in acetone to prepare a methyltrichlorosilane solution of a certain concentration, wherein the mass ratio of methyltrichlorosilane, glacial acetic acid and acetone is 20:5:55;
[0071] 5) After the hydrolyzed fiber membrane is placed in a methyltrichlorosilane solution for 2 hours, it is transferred to a constant temperature and humidity chamber at 50°C and 70% humidity for 50 minutes. After that, it is taken out and dried at 28°C to obtain a nanofiber membrane constructed from Janus-like nanofibers.
[0072] Example 5
[0073] 1) Weigh a certain amount of allyloxytrimethylsilane and polyurethane and dissolve them in N,N-dimethylformamide to prepare a mixed spinning solution, wherein the mass ratio of allyloxytrimethylsilane, polyurethane and N,N-dimethylformamide is 1.5:25:73.5;
[0074] 2) Fiber membranes are prepared using electrospinning technology;
[0075] 3) Hydrolyze the fiber membrane in water at 30°C for 2 hours;
[0076] 4) Weigh a certain amount of dimethyldichlorosilane and hydrochloric acid, and dissolve them in chloroform to prepare a dimethyldichlorosilane solution of a certain concentration, wherein the mass ratio of dimethyldichlorosilane, hydrochloric acid and chloroform is 15:5:80;
[0077] 5) After hydrolyzing the fiber membrane, place it in a dimethyldichlorosilane solution for 15 minutes, then transfer it to a constant temperature and humidity chamber at 70°C and 90% humidity for 2 hours. Remove it and air dry it at 50°C to obtain the nanofiber membrane constructed from Janus-like nanofibers.
[0078] Comparative Example 1
[0079] A certain amount of polyacrylonitrile was dissolved in N,N-dimethylacetamide to prepare a spinning solution with a concentration of 5 wt%. Nanofiber membranes were then prepared by electrospinning.
[0080] Comparative Example 2
[0081] A certain amount of vinyltriethoxysilane and polyacrylonitrile were weighed and dissolved in N,N-dimethylacetamide to prepare a mixed spinning solution, wherein the mass ratio of vinyltriethoxysilane and polyacrylonitrile dissolved in N,N-dimethylacetamide was 1:4:95; nanofiber membranes were prepared by electrospinning technology.
[0082] Performance Testing: The inventors conducted performance tests on the polyacrylonitrile nanofiber membranes constructed from Janus-like structure nanofibers obtained in Comparative Examples 1, 2, and 1-5 of this invention. The test results for Examples 1, 1, and 2 are shown in the figures below. Figures 1-7 As shown, where Figure 1 This is a scanning electron microscope (SEM) image of the polyacrylonitrile nanofiber membrane prepared in Comparative Example 1 of this invention. Figure 2 This is a scanning electron microscope (SEM) image of the vinyltriethoxysilane-doped polyacrylonitrile nanofiber membrane prepared in Comparative Example 2 of this invention. Figure 3 This is a scanning electron microscope (SEM) image of a polyacrylonitrile nanofiber membrane constructed from Janus-like nanofibers obtained in Example 1 of this invention. Figure 4The thickness of the hydrophobic layer of the polyacrylonitrile nanofiber membrane constructed from the Janus-like structure nanofibers obtained in Example 1 of this invention. Figure 5 The figure shows the relationship between the water contact angle (WCA) of the nanofiber membranes prepared in Comparative Examples 1, 2, and 1 of this invention and time. Figure 6 The underwater oil contact angle (UOCA) of the nanofiber membranes prepared in Comparative Examples 1, 2, and 1 of this invention is shown. Figure 7 The long-term separation flux of the polyacrylonitrile nanofiber membranes constructed from the Janus-like structure nanofibers obtained in Comparative Examples 1, 2 and 1 of this invention is shown.
[0083] from Figure 1 It can be seen that the polyacrylonitrile nanofiber membrane prepared in Comparative Example 1 is composed of randomly stacked nanofibers with a diameter of approximately 500 nm; from Figure 2 It can be seen that the vinyltriethoxysilane-doped polyacrylonitrile nanofiber membrane prepared in Comparative Example 2 is composed of randomly stacked nanofibers with a diameter of approximately 500 nm. Figure 3 It can be seen that, with Figure 1 and Figure 2 In comparison, the morphology and fiber diameter of the polyacrylonitrile nanofiber membrane constructed from the Janus-like nanofibers prepared in Example 1 remained basically unchanged. The nanofiber membrane was composed of random stacking of nanofibers with a diameter of about 500 nm.
[0084] from Figure 4 It can be seen that the hydrophobic layer thickness of the polyacrylonitrile nanofiber membrane constructed from the Janus-like nanofibers prepared in Example 1 is 8.6 nm.
[0085] from Figure 5 and Figure 6 It can be seen that: the water contact angle of the polyacrylonitrile nanofiber membrane constructed from Janus-like nanofibers prepared in Example 1 is 0°, the wetting time is 7.5s, and the underwater oil contact angle is 131°; while the water contact angle of the polyacrylonitrile nanofiber membrane prepared in Comparative Example 1 is 0°, the wetting time is 1.5s, and the underwater oil contact angle is 148°; the water contact angle of the vinyltriethoxysilane-doped polyacrylonitrile nanofiber membrane prepared in Comparative Example 2 is 0°, the wetting time is 4.5s, and the underwater oil contact angle is 132°.
[0086] from Figure 7 It can be seen that the polyacrylonitrile nanofiber membrane constructed from the Janus-like nanofibers prepared in Example 1 exhibits a permeation flux of 1600 Lm for hexadecane in water under cross-flow filtration conditions. -2 h -1 bar -1The separation efficiency is above 99.96%, but its permeation flux can still reach 700 L / m² after more than 10 hours of separation. -2 h -1 bar -1 The above results show that, under dead-end filtration conditions, the oil recovery rate reaches over 85%; while the polyacrylonitrile nanofiber membrane prepared in Comparative Example 1, under cross-flow filtration conditions, exhibits a permeation flux of 2100 L / m³ for hexadecane in water. -2 h -1 bar -1 The separation efficiency was above 99.96%, but the permeation flux dropped to 0 within 4 hours. The vinyltriethoxysilane-doped polyacrylonitrile nanofiber membrane prepared in Comparative Example 2, under cross-flow filtration conditions, achieved a permeation flux of 1800 L / m³ for hexadecane in water. -2 h -1 bar -1 The separation efficiency is above 99.90%, but its permeation flux drops to 0 within 1.5 hours.
[0087] Furthermore, the detection results of Examples 2-5 of the present invention are as follows:
[0088] Example 2: The obtained nanofiber membrane was composed of randomly stacked nanofibers with a diameter of approximately 200 nm; its water contact angle was 0°, wetting time was 5.5 s, and underwater oil contact angle was 120°. Under cross-flow filtration conditions, the membrane achieved a permeation flux of 1500 Lm for hexadecane in water. -2 h -1 bar -1 The separation efficiency is above 99.96%, but its permeation flux can still reach 800 Lm after more than 20 hours of separation. -2 h -1 bar -1 The above. Under dead-end filtration conditions, its oil recovery rate reaches over 80%.
[0089] Example 3: The obtained nanofiber membrane was composed of randomly stacked nanofibers with a diameter of approximately 100 nm; its water contact angle was 0°, wetting time was 6.5 s, and underwater oil contact angle was 125°. Under cross-flow filtration conditions, the membrane achieved a permeation flux of 1700 Lm for hexadecane in water. -2 h -1 bar -1 The separation efficiency is above 99.96%, but its permeation flux can still reach 1000 Lm after more than 15 hours of separation. -2 h -1 bar -1 The above results show that, under dead-end filtration conditions, the oil recovery rate reaches over 82%.
[0090] Example 4: The obtained nanofiber membrane is composed of randomly stacked nanofibers with a diameter of approximately 800 nm; its water contact angle is 0°, wetting time is 10 s, and underwater oil contact angle is 120°. Under cross-flow filtration conditions, the membrane achieves a permeation flux of 1400 Lm for hexadecane in water. -2 h -1 bar -1 The separation efficiency is above 99.95%, but its permeation flux can still reach 600 Lm after more than 17 hours of separation. -2 h -1 bar -1 The above. Under dead-end filtration conditions, its oil recovery rate reaches over 88%.
[0091] Example 5: The obtained nanofiber membrane was composed of randomly stacked nanofibers with a diameter of approximately 400 nm; its water contact angle was 0°, wetting time was 2 s, and underwater oil contact angle was 145°. Under cross-flow filtration conditions, the membrane achieved a permeation flux of 1900 Lm for hexadecane in water. -2 h -1 bar -1 The separation efficiency is above 99.95%, and the permeation flux can still reach 1200 Lm after more than 40 hours of separation. -2 h -1 bar -1 The above. Under dead-end filtration conditions, its oil recovery rate reaches over 90%.
[0092] The results show that the present invention provides a destination for the aqueous and oil phases in an emulsion by constructing an ultrathin hydrophobic layer on the outer surface of hydrophilic nanofibers. The hydrophilic nanofibers ensure that the aqueous phase can wet the membrane substrate and allow the continuous aqueous phase to permeate through the membrane pores. The hydrophobic layer adsorbs and diffuses demulsified oil droplets along the nanofiber surface, freeing up membrane pore space and thus ensuring a relatively stable flux of the continuous phase (water). More importantly, the shear force of the aqueous phase can directly act on the aggregated oil phase. Simultaneously, due to the directional transport effect, water can transfer to the middle of the hydrophobic layer and the nanofiber substrate, which will further facilitate the release of oil from the membrane, ultimately achieving efficient demulsification, long-lasting anti-fouling oil-water separation, and simultaneous recovery of both oil and aqueous phases.
[0093] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a nanofiber membrane, characterized in that, The preparation method specifically includes the following steps: S1. Weigh out the first silane monomer and the hydrophilic polymer and dissolve them in solvent A to obtain a mixed spinning solution; S2. The mixed spinning solution obtained in step S1 is used to prepare a fiber membrane by electrospinning, phase inversion or melt spinning. S3. Hydrolyze the fiber membrane obtained in step S2 to obtain a hydrolyzed fiber membrane; S4. Weigh out the second silane monomer and the inorganic acid and dissolve them in solvent B to obtain a second silane monomer solution; S5. Place the hydrolyzed fiber membrane obtained in step S3 into the second silane monomer solution obtained in step S4, then transfer it to a constant temperature and humidity chamber for reaction, take it out and air dry to obtain a nanofiber membrane. In step S1, the first silane monomer is selected from one or more of allyltriethoxysilane, (3-epoxypropoxypropyl)triethoxysilane, vinyltriethoxysilane, and allyloxytrimethylsilane; the hydrophilic polymer is selected from one or more of polyacrylonitrile, polyvinyl alcohol, polylactic acid, polyurethane, polymethyl methacrylate, polypropylene, and polyvinyl chloride; and solvent A is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, toluene, acetone, n-hexane, and water. In step S4, the second silane monomer is selected from one or more of methyltrichlorosilane, dimethyldimethoxysilane, dimethyldichlorosilane, dodecylpentasiloxane, and diphenyldichlorosilane; the inorganic acid is selected from one or more of citric acid, glacial acetic acid, hydrochloric acid, sulfuric acid, and nitric acid; and the solvent B is selected from one or more of ethanol, isopropanol, methanol, n-hexane, toluene, dichloromethane, chloroform, and acetone.
2. The method for preparing the nanofiber membrane as described in claim 1, characterized in that, In step S1, the mass ratio of the first silane monomer, the hydrophilic polymer, and solvent A is (0.5-2):(4-30):(70-95).
3. The method for preparing the nanofiber membrane as described in claim 1, characterized in that, In step S3, the hydrolysis parameters are as follows: the hydrolysis temperature is 20-80℃, and the hydrolysis time is 20-120min.
4. The method for preparing the nanofiber membrane as described in claim 1, characterized in that, In step S4, the mass ratio of the second silane monomer, the inorganic acid and the solvent B is (1-30):(1-10):(60-98).
5. The method for preparing the nanofiber membrane as described in claim 1, characterized in that, The specific steps of step S5 are as follows: the nanofiber membrane after hydrolysis in step S3 is placed in the second silane monomer solution obtained in step S4 for 1-60 min, and then transferred to a constant temperature and humidity chamber with a temperature of 20-80℃ and a humidity of 10-90% for 10-180 min. After that, it is taken out and dried at 10-50℃ to obtain the nanofiber membrane.
6. A nanofiber membrane prepared by any one of the preparation methods according to claims 1-5, characterized in that, The nanofiber membrane has a heterogeneous wettability interface, which includes a hydrophilic nanofiber body and a hydrophobic layer wrapped around the surface of the hydrophilic nanofiber. The hydrophobic layer is a nanolayer with a thickness of less than 10 nm, and the diameter of the nanofibers in the nanofiber membrane is 20-1000 nm.
7. The nanofiber membrane as described in claim 6, characterized in that, The parameters of the nanofiber membrane are as follows: the water contact angle is 0°, the water droplet wetting time is less than 10s, and the underwater oil contact angle is greater than 120° and less than 150°.
8. An application of the nanofiber membrane as described in claim 6 or 7 in the field of oil-water separation.
Citation Information
Patent Citations
Asymmetric ultra-hydrophilic / hydrophobic dual-property polymer membrane and preparation method thereof
CN106268355A
Nanometer fiber composite film, and preparation method and applications thereof
CN110053334A